THE COURTS OF REASON: IN SEARCH OF THE ULTIMATE JUSTIFICATION - Harshavardhan; Harshit, Kumar (NLUJ, 2024)
The Supreme Court has deliberately kept the judiciary out of the ambit of ‘State’ under Article 12 but the functional justification it provides for such a move does not correspond to how the common man perceives its role in the state machinery. It does not provide an ultimate understanding as to why such a position is taken. It is in this search that we turn to higher norms. The moment we leave the womb of the Court’s reasoning, the sceptic raises his head and asks what then, in turn, justifies this higher norm. This leads us to the problem of infinite regress which offers no way out. It is in this position that we turn to the understanding of legitimacy and justification in an attempt to make sense of the state machinery. Disillusioned by the absence of a primordial norm, we turn towards the art of persuasion and the implications flowing from it. Lastly, we delve into state structure and judiciary’s role to understand the deeper interests that the Court is trying to protect.
Keywords: Article 12; Infinite Regress; Basic Norm; Legitimacy; Judiciary